2008
DOI: 10.1080/09585170802357504
|View full text |Cite
|
Sign up to set email alerts
|

Conceptions of assessment: trainee teachers' practice and values

Abstract: This study examines the values and practice in relation to assessment of a sample of 220 trainee teachers studying for a Postgraduate Certificate in Education, an initial teacher training and education (ITET) course, at the University of Cambridge, UK. The survey instrument was drawn from James and Pedder (2006), and was composed of questionnaire items that sought to elicit how trainees valued different classroom assessment practices, and the extent to which their own teaching complied with such values. The st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
27
0
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 29 publications
3
27
0
3
Order By: Relevance
“…Even though there is strong evidence about the importance of classroom assessment, studies have reported that teacher candidate preparation has been less than adequate and that preservice assessment teaching (when it occurs) can also be diluted through teaching practice experiences and/or particular personal characteristics of the teacher candidates themselves (Campbell, 2013). Furthermore, when they begin teacher education, teacher candidates generally demonstrate negative emotions about assessment (Crossman, 2007;Smith et al, 2014) have conceptions of assessment that are from those of practicing teachers (Brown and Remesal, 2012;Chen and Brown, 2013) and while they might value the ideals of formative assessment they do not know how to implement it (Winterbottom et al, 2008).…”
Section: Previous Studies Regarding Teacher Preparation For Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Even though there is strong evidence about the importance of classroom assessment, studies have reported that teacher candidate preparation has been less than adequate and that preservice assessment teaching (when it occurs) can also be diluted through teaching practice experiences and/or particular personal characteristics of the teacher candidates themselves (Campbell, 2013). Furthermore, when they begin teacher education, teacher candidates generally demonstrate negative emotions about assessment (Crossman, 2007;Smith et al, 2014) have conceptions of assessment that are from those of practicing teachers (Brown and Remesal, 2012;Chen and Brown, 2013) and while they might value the ideals of formative assessment they do not know how to implement it (Winterbottom et al, 2008).…”
Section: Previous Studies Regarding Teacher Preparation For Assessmentmentioning
confidence: 99%
“…Even though there is strong evidence about the importance of classroom assessment, studies have reported that teacher candidate preparation has been less than adequate and that preservice assessment teaching (when it occurs) can also be diluted through teaching practice experiences and/or particular personal characteristics of the teacher candidates themselves (Campbell, 2013). Furthermore, when they begin teacher education, teacher candidates generally demonstrate negative emotions about assessment (Crossman, 2007;Smith et al, 2014) have conceptions of assessment that are from those of practicing teachers (Brown and Remesal, 2012;Chen and Brown, 2013) and while they might value the ideals of formative assessment they do not know how to implement it (Winterbottom et al, 2008).Recently though, studies have begun to tackle how teacher candidates learn about, and to enact, formative assessment (for example, Buck et al, 2010;Eyers, 2014;Smith et al, 2014). In a review of this literature (Hill and Eyers, 2016) four main influences were found: the teacher candidate conceptions that underpin such learning (for example, Brown, 2011;Brown and Remesal, 2012); the relationship between preservice assessment teaching and teacher candidate learning (for example, Buck et al, 2010;Siegel and Wissehr, 2011;DeLuca et al, 2012); the practical use by teacher candidates of assessment in classrooms during preparation (Graham, 2005;DeLuca and Klinger, 2010;Nolen et al, 2011; and others); and other factors such as personal dimensions (Eyers, 2014;Jiang, 2015), layered contexts (Nolen et al, 2011;Jiang, 2015) and broader policy and societal issues (Smith et al, 2014).…”
mentioning
confidence: 99%
“…However, there is evidence that both prospective teachers' and teachers' conceptions about assessment can be identified in terms of their assessment-related values and practices (e.g., Winterbottom et al, 2008), signifying that the same may also be true for their conceptions about teaching/learning due to the interrelated nature of these conceptions (McNeill, 1996;Oliva, 1997).…”
Section: Literature Review and Conceptual Framework Conceptions Aboutmentioning
confidence: 99%
“…School and university mentors play an influential role in forming trusting communities of practice where student teachers can learn to be inquiring about their motives, decisions, actions and outcomes for pupils (Timperley, Kaser & Halbert, 2014). Professional learning may be enhanced further if mentors are inquiring themselves, since they are more likely to give student teachers the agency they need to seek evidence, adapt their practices and critically reflect on the outcomes (Winterbottom, et al, 2008). Britzman (2000) concluded that self-knowledge can be difficult to face.…”
Section: Related Literaturementioning
confidence: 99%